To Translate or not To Translate: Narratives and Translation in the UK Home Office. - Ruiz Cortés, Elena (Iconesoft Edizioni Gruppo Radivo Holding, 2020)
Translation services in migratory contexts have not been traditionally depicted as an advantage for British society. In fact, the provision of such services in these contexts has been seen as a social and economic burden. In this paper, we aim to connect how the translation and migration narratives that have emerged in the UK over the years have impacted on the provision of translation by the ministerial department responsible for immigration in this country, i.e., the Home Office (HO). As a first stage of an on-going project, the methodological concept of domain is used to investigate the provision of translation services during EU immigration procedures at the HO from a descriptive standpoint. Here, we will examine to what extent translations are available at this key administrative stage at the outset of the migratory experience when migrants, with and without language barriers, need to communicate their narratives correctly in order to be granted EU residence documentation. Our initial findings suggest that both EU migration and translation narratives seem to have influenced an HO translation policy of nontranslation, a policy that needs to be further addressed in the near future.
Keywords: Traducción - Aspectos sociales; Emigración e inmigración; Translation policy; Home office; Migration narratives; Translation narratives; EU immigration procedures